How to Bring Computational Thinking Approach to The Non-Computer Science Student’s Class??? - Hervin Maulina; Abdurrahman Abdurrahman; Ismu Sukamto (Jurnal Pembelajaran Fisika, 2021)
Computational Thinking (CT) skill is the ability to solve problems with computer thinking. In addition, CT can be seen as a structured and systematic approach that can be implemented in learning. This study aims to bring the computational thinking approach to the non-computer science student’s class and involved 35 undergraduate students of physics education in the computational physics course. The research method used was the mixed method sequential explanatory design (Creswell & Plano Clark, 2011), with the following design. Broadly speaking, the flow of the mixed-method research method with an explanatory sequential design in this study includes the collection of quantitative data obtained from student self-evaluation instruments related to the understanding of the CT approach stage. The results showed that the Computational Thinking (CT) approach can be applied to non-computer science students in online learning which includes 6 stages of implementation and 6 stages of implementation. Other results indicate that this method can be used in improving student CT skills.Keywords: Computational thinking, physics, problem-solvingDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202109